The Impact of the Pentahelix Model of Disaster Management on Community Satisfaction through the Leadership Style of the Mayor of Palu - Erdiyansyah Erdiyansyah; Slamet Riadi; Muhammad Nawawi; Mohamad Irfan (MASI Mandiri Edukasi, 2026)
Effective disaster response in Palu City continues to face challenges in multi-stakeholder coordination, which affects community satisfaction. This study aims to analyze the impact of the pentahelix model of disaster management on community satisfaction and to examine the moderating role of the Palu Mayor’s leadership style. The study employs a quantitative method with a population of 5,514 stakeholders and affected residents, and a sample of 210 respondents selected via proportional stratified random sampling. Primary data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results of the hypothesis testing confirm that the pentahelix model has a positive and significant effect on community satisfaction (β = 0.430; p < 0.001), as does situational leadership style (β = 0.420; p < 0.001). A crucial finding indicates that leadership style significantly strengthens the relationship between the pentahelix model and community satisfaction (β = 0.275; p < 0.001), with the structural model exhibiting strong explanatory power (R² = 0.622) and adequate predictive relevance (Q² = 0.378). It is concluded that pentahelix synergy achieves optimal effectiveness only when catalyzed by adaptive, transparent, and goal-oriented leadership. These findings have practical implications for the Palu City Government, which should institutionalize multi-stakeholder collaboration forums, strengthened by situational leadership capacity, to enhance public legitimacy and the resilience of disaster governance.